A study on Problems and Prospects of Freshwater Fish Farming, Agra (India): Challenges and Opportunities for Freshwater Fish Farming in Agra, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current A study was done. in Agra. A basic 30 people at randomfarmers was chosen, andthe participatory rural assessment method was used to help them identify the challenges they were havingwith fish farming in that city. A total of six important sources of informationwere chosen. Farmers facetechnical and infrastructural challenges, according to the report. The primary technical issues are highfeed costs, a lack of high-quality seeds, and biological dangers. Credit, marketing, pond ownership,insufficient technical expertise, and limited expansion connectivity are all examples of infrastructureissues. Scientists might learn more about the technological locational issues and, as a result, recommendhow to construct the experiment by giving need-based solutions. Farmers' infrastructure is also criticalfor the successful application of scientific aquaculture operations.The current situation, issues, andPossibilities of inland fishing in Agra are discussed in this article